2021
DOI: 10.1080/23311975.2021.1908745
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the green purchase behaviour of millennials: An emerging country perspective

Abstract: The study investigates the determinants of green purchase behaviour amongst the millennial cohort in an emerging market of South Africa. The research was theoretically grounded on the diffusion of innovation and the theory of planned behaviour models. A descriptive quantitative research design was followed and primary data was gathered using a self-administered questionnaire. A total of 355 complete responses were suitable for analysis. A partial least squares structural equation modelling technique was used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 57 publications
0
19
0
Order By: Relevance
“…In a variety of green/pro-environmental fields, TPB has been hailed as a crucial theoretical lens for anticipating consumer intention as well as behaviour ( Dilotsotlhe, 2021 ). In more detail, the theory's applicability and robustness have been demonstrated in a number of studies looking at recycling behaviours ( Khan et al, 2019 ), green apparel ( Nam et al, 2017 ), energy efficient products ( Gao et al, 2017 ), organic food choices ( Rana and Paul, 2017 ), green hotels and restaurants ( Chen and Tung, 2014 ), and environmentally friendly cars ( Chen and Peng, 2012 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In a variety of green/pro-environmental fields, TPB has been hailed as a crucial theoretical lens for anticipating consumer intention as well as behaviour ( Dilotsotlhe, 2021 ). In more detail, the theory's applicability and robustness have been demonstrated in a number of studies looking at recycling behaviours ( Khan et al, 2019 ), green apparel ( Nam et al, 2017 ), energy efficient products ( Gao et al, 2017 ), organic food choices ( Rana and Paul, 2017 ), green hotels and restaurants ( Chen and Tung, 2014 ), and environmentally friendly cars ( Chen and Peng, 2012 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Perceived behavioral control was found to have a significant and positive influence on purchase behaviour in two studies (Wang et al, 2014;Du & Han, 2012). However, Dilotsotlhe (2021) revealed that perceived behavioral control had no impact on predicting adoption behaviour.…”
Section: Theory Of Planned Behaviormentioning
confidence: 94%
“…Three items of SMI were taken from Pop et al (2020) and Saeed et al (2019). Att was measured using four items taken from Dhir et al (2021) and Dilotsotlhe (2021). Three items adopted from Paul et al (2016) and Shukla (2019) were used to check SN.…”
Section: Methodsmentioning
confidence: 99%
“…Att was measured using four items taken from Dhir et al. (2021) and Dilotsotlhe (2021). Three items adopted from Paul et al.…”
Section: Methodsmentioning
confidence: 99%